Caring Dads? Universal Childcare, Paternity Leave and Fathers' Involvement - Mathias Huebener; Malin K. Mahlbacher; Sophia Schmitz (Institute of Labor Economics (IZA), 2024)
Increasing fathers' involvement in childcare is seen as an important strategy to reduce women's child penalties in the labour market. However, very little is known about the extent to which family policies can enhance fathers' engagement in domestic work. This paper examines the impact of the combined availability of universal childcare and paternity leave on fathers' involvement. We exploit quasi-experimental variation in the regional availability of childcare for children under three, resulting from the introduction of a universal childcare entitlement in Germany. We estimate generalised difference-in-differences models and confirm that children enter childcare significantly earlier. Fathers become more likely to take paternity leave with the expectation of mothers entering the labour market sooner. Yet, this leave is mainly taken for the minimum period, together with the mother, and towards the end of the first year. Fathers' subsequent roles as caregivers, as well as their labour market outcomes, remain largely unaffected. Overall, increased childcare availability primarily substitutes maternal care; significant family policy efforts could not immediately alter fathers' caregiving responsibilities within the family.
Keywords: J13; J16; J18; J22; D13; 330; public childcare; family policies; parental leave; paternal involvement